Hubungan Jalur Penerimaan Mahasiswa Baru Akuntansi Terhadap Prestasi Akademik - Abdillah Bela Nuswantoro; Unti Ludigdo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study aims to determine how the relationship between the university recruitments way for academic achievement of the students during the process of taking the course. Academic achievement in this study is proxied to the accounting value of the score courses, GPA, and the total credits that have been taken. The population in this study were students of the Faculty of Economics and Business Brawijaya University class of 2009. The data were drawn from primary data through questionnaires and secondary data from the Recording Faculty of Economics and Business Brawijaya University. Questionnaires were distributed for 150 pieces, but only 130 pieces that fulfill the criteria of the study sample is purposive sampling. This study used analysis of One-Way ANOVA in analyzing research data. Based on the test results of One-Way ANOVA analysis of the questionnaires that researchers get the data it can be concluded that the students are accepted through SNMPTN have high academic achievement, academic achievement of students who received PSB Akademik better academically than students who received the PSB Non-akademik, and there was no significant difference in academic achievement between students who received in SPMK with students who received in SPKS. Keywords : university recruitments way, GPA, credits, and the value of score accounting courses.